Matter - Cooper, Chris (New York : Dorling Kindersley, 1992)
Examines the elements that make up the physical world and the properties and behavior of different kinds of matter.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
7.5
4-6
5-8
Keywords: Atoms -- Juvenile literature; Matter -- Constitution -- Juvenile literature; Matter -- Properties -- Juvenile literature; Molecules -- Juvenile literature; Atoms; Matter; Molecules; Atoms; Matter; Molecules